Surveillance technologies as Instruments of discipline in the elite sports coaching context: A cautionary post-structural commentary - Jones, L.; Toner, J. (Sensoria - A journal of mind, brain and culture, 2016)
The use of surveillance technologies as tools to encourage performance enhancement has become an accepted component of elite coaching. Those from the communities of sports physiology, psychology and biomechanics who promote the application of surv eillance technologies have reported multiple benefits for the athlete. Conversely, several socio-cultural studies have suggested that surveillance technologies can lead to an oppressive mechanism of control over the athlete, significantly altering the role and responsibilities of the contemporary coach. In this critical commentary we use a post-structural position and adopt Foucault`s disciplinary analysis to contribute to the ongoing debate surrounding the use of surveillance technology in sport. Specifically, we achieve this by labelling surveillance technologies in sport as what Foucault (1977) might call, instruments of discipline, and by explaining the impact they have upon the working coach and the skilled athlete. We present some suggestions surrounding how to most appropriately utilise surveillance technologies in a sports coaching context and conclude by warning against a binary consideration of the use of technology as either good or bad